Pengaruh Profitabilitas, Asset Tangibility, Dan Ukuran Perusahaan Terhadap Struktur Modal (Studi Empiris Pada Perusahaan Sub Sektor Property Dan Real Estate Di Bursa Efek Indonesia Tahun 2020-2023) - Ayu Khairunnisa; Retno Puji Astuti (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2025)
The purpose of this study is to measure and collect empirical evidence regarding the effect of profitability, asset tangibility, and company size on capital structure. The object of this study is the property and real estate sector agencies listed on the Indonesia Stock Exchange in 2020-2023. With all 93 agencies in the property and real estate sector being the research population. Purposive sampling is carried out to determine the sample, as a result the sample of this study totals 39 agencies that are in line with the requirements. The data analysis technique used is panel data regression analysis, and the best model obtained is the fixed effect model with the help of Eviews 12 software. The results of this study found that profitability has a negative influence on capital structure, asset tangibility has a positive influence on capital structure. Meanwhile, firm size has no influence on capital structure.